Sobre los 40 años del Código Civil: una mirada histórica - Vidal Ramírez, Fernando (2024)
As part of the 40th anniversary of the Civil Code, Dr. Vidal Ramirez, one of the few members of the Civil Code Reform Commission still alive, tells us unpublished stories about the experience of reform and codification of the Civil Code of 1984. He also recalls the other members of the Reform Commission, as well as the challenges they faced to achieve what is now the most important civil law.